Productivity Improvement Through Lean Six Sigma In Pharmaceutical Manufacturing: A Narrative Review - Alifiya, Fhahira; Chairun Wiedyaningsih, Chairun; Bondan Ardiningtyas, Bondan (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
This review examined Lean Six Sigma's (LSS) impact on pharmaceutical manufacturing productivity. Five relevant studies were identified, though targeted research in this area was limited. The studies consistently showed LSS's positive influence, highlighting its effectiveness in boosting productivity, reducing inefficiencies and waste, improving delivery, and generating cost savings. The DMAIC cycle's importance and the correlation between Six Sigma and productivity were emphasized. Lean integration (like value stream mapping) was crucial for waste elimination. One study linked lean production with sustainability. While the literature supports LSS benefits, further research is needed to explore implementation strategies and challenges. The studies confirm LSS as a powerful tool for pharmaceutical companies seeking operational optimization, quality enhancement, and productivity improvement.